Grinding damage characteristics of silicon carbide ceramics - Hui YE; Jiafu XIE; Anjie NI (Jin'gangshi yu moliao moju gongcheng)
ObjectivesTo explore the grinding damage mechanism and surface/subsurface damage distribution law of silicon carbide ceramics. MethodsCombined with single-particle scratching experiments, grinding experiments, and finite element simulation analyses, the critical stress value of the plastic-brittle transition of the material, as well as the trend of the influence of the grinding parameters on the damage distribution, are clarified. ResultsThe ultimate fracture strength of the silicon carbide ceramics used in this experiment is about 344 MPa, and the grain boundary fracture strength is about 25.9 MPa. Both the experimental and simulation results show that the microstructure of the material plays different roles under different loads. When the contact stress is less than the critical fracture strength of the grain boundaries, the grain boundary structure plays a viscous role, consuming stresses to inhibit the expansion of cracks. With a further increase in load, although not reaching the critical stress value of the grain boundaries, the cracks are still generated but not as severe. Further increase in load, although the material fracture limit is not reached, the material surface will still exhibit cracks and pits due to microstructural damage caused by grain boundaries, graphite, and pores. When the contact stress exceeds the critical strength of the material and the grain boundaries, the microstructure promotes the growth of cracks, further expanding the damage area of the SiC ceramics. In the paper, through the optimization of the grinding process parameters, the best parameters for achieving the minimum grit undeformed chip thickness and grinding force are determined, thus minimizing the percentage of material surface damage and the depth of subsurface damage, which are 0.396% and 4.768 μm, respectively. Compared with the worst parameters, the damage values are only 16.01% and 13.22% of their respective counterparts. ConclusionsThe process of material grinding damage is similar to that of single grit scratch damage, which progresses three stages: plastic removal, plastic-brittle removal, and brittle removal. The grinding force, the change in maximum grit thickness without deformation, and the extent of material damage all tend to increase with the increase of feed rate and grinding depth, and decrease with the increase of grinding wheel speed. The microstructure of ceramic materials is an important reason for their machining susceptibility to machining damage. In order to achieve low-defect processing of silicon carbide ceramics, it is not only necessary to optimize the grinding process parameters but also to consider the role of the microstructure. The experimental results provide theoretical guidance for achieving low-damage and high-quality processing.